2013
DOI: 10.1186/1471-2474-14-75
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of the domino effect in osteoporotic vertebral compression fractures through short-segment fixation with intravertebral expandable pillars compared to percutaneous kyphoplasty: a case control study

Abstract: BackgroundOsteoporotic vertebral compression fracture is the leading cause of disability and morbidity in elderly people. Treatment of this condition remains a challenge. Osteoporotic vertebral compression fractures can be managed with various approaches, but each has limitations. In this study, we compared the clinical outcomes obtained using short-segment fixation with intravertebral expandable pillars (I-VEP) to those obtained with percutaneous kyphoplasty in patients who had suffered vertebral compression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Three studies reported adjacent segment 39,44 or disc degeneration, 33 and only 1 study reported the kyphosis angle proximal to the index level. 41 Since not a single study reported complete information on all the parameters of interest, we attempted to contact all authors to request further information. A total of 4 authors responded to our mails but only 3 were able to provide additional information.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three studies reported adjacent segment 39,44 or disc degeneration, 33 and only 1 study reported the kyphosis angle proximal to the index level. 41 Since not a single study reported complete information on all the parameters of interest, we attempted to contact all authors to request further information. A total of 4 authors responded to our mails but only 3 were able to provide additional information.…”
Section: Discussionmentioning
confidence: 99%
“…In 7 studies, screws were augmented, [29][30][31][32][33][34][35] in 21 studies, screws were nonaugmented, 27,28,[36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54] and 4 studies compared outcomes of augmented versus nonaugmented screws. [55][56][57][58] Indications, that is, degenerative disease or fracture, were equally distributed in the studies on augmented and nonaugmented screws (Table 4).…”
Section: Eligible Literaturementioning
confidence: 99%
“…Conservative treatment for compression fractures has not been suggested, as it fails to restore the vertebral body to its origin height. Additionally, pain and spinal deformity are not improved or corrected, and the domino effect follows rapidly after the rst VCF [10]. This effect is a direct consequence of the mechanical variations that affect the spine when physiological curves are modi ed [11].…”
Section: Discussionmentioning
confidence: 99%
“…We recently introduced an intra-vertebral expandable pillars (I-VEPs) procedure, and demonstrated that it is effective in reducing collapsed vertebra and in providing fitting fixation for injured vertebra [17]. Posterior short-segment fixation with I-VEPs is an alternative procedure to relieve symptomatic local back pain and avoid a global domino effect in an osteoporotic kyphotic spine [18].…”
Section: Introductionmentioning
confidence: 99%
“…In other words, cementing should be treated as an augmentation technique and not as a gold standard for the permanent treatment of fractures.I-VEPs are made of titanium alloy due to its excellent biocompatibility and are designed as a hollow threaded cylinder filled with autologous bone graft. After good open reduction with adequate serial dilatation, the biological intra-vertebral body fixation of an I-VEP is used to reconstruct the compressed vertebra through internal mechanical support, and bony fusion is encouraged with enveloped bone chips[17] [18]. PRO-DENSE™, a fully synthetic composite material made from calcium sulphate (CaSO 4 ) and calcium phosphate (CaPO 4 ), is strong composite-like bone cement with good bone regeneration capacity[38]…”
mentioning
confidence: 99%